2005
DOI: 10.1002/gene.20133
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of the sciellin gene resulted in normal development and maturation

Abstract: Summary: Sciellin, together with other precursor proteins, was cross-linked by transglutaminase 1 to form the cornified envelope, an essential component of the physical barrier of the epidermis and stratified squamous epithelia. To more fully understand the function of sciellin in cornified envelope formation, we generated sciellin null mice. The mice appeared normal in their development and maturation and there were no structural features that distinguished them from littermate controls. Isolated cornified en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(51 reference statements)
0
6
0
1
Order By: Relevance
“…The specific function of this gene in human skin is not known to date, but deletion of this gene in mice did not affect normal barrier function 54.…”
Section: Discussionmentioning
confidence: 96%
“…The specific function of this gene in human skin is not known to date, but deletion of this gene in mice did not affect normal barrier function 54.…”
Section: Discussionmentioning
confidence: 96%
“…Although the expressions of other claudins have been shown to be influenced by phorbol ester exposure to murine skin (Arabzadeh et al, 2008), expression of claudin 23 in skin was never previously reported. The expression of sciellin has not been described in any pathological skin conditions; in contrast, sciellin null mice have normal skin development and structure (Baden et al, 2005). Downregulation of SQLE indicates altered epidermal cholesterol biosynthesis.…”
Section: Interpretation Of the Initial Epidermal Response To Mild Irrmentioning
confidence: 96%
“…Sciellin was initially characterized in a screen of antigens generated from human keratinocyte CE fragments as a highly insoluble CE precursor and transglutaminase substrate [40]. Subsequently, sciellin was shown to contain a proline-rich N-terminal domain, a central 16 repeat glutamine- and lysine-rich motif—the transglutaminase substrate—and a C-terminal LIM domain [13,15]. LIM domains, which are protein-interaction motifs, have been demonstrated in other proteins associated with the cytoskeleton and biomechanical stress in VSMCs [33,41].…”
Section: Discussionmentioning
confidence: 99%
“…Sciellin contains a core of conserved repeats and a unique proline-rich N-terminal domain that are proposed to serve a structural role. Furthermore, it possesses a C-terminal LIM domain that is believed to be a protein-interaction domain, possibly bestowing a scaffolding function on sciellin [1315]. Periplakin, a member of the plakin family of proteins, is enriched in desmosomes where it acts as a mediator of intermediate filament assembly [16,17].…”
Section: Introductionmentioning
confidence: 99%